Oxytocin effects on pain perception and pain anticipation - Herpertz, Sabine; Schmitgen, Mike; Roth, Corinna; Wolf, Robert Christian; Bertsch, Katja; Flor, Herta; Grinevich, Valéry; Boll, Sabrina (The journal of pain, 2019)
There is an ongoing debate whether the neuropeptide oxytocin (OT) modulates pain processing in humans. This study differentiates behavioral and neuronal OT effects on pain perception and pain anticipation by using a Pavlovian conditioning paradigm. Forty-six males received intranasally administered OT in a randomized, double-blind, placebo-controlled group design. Although OT exerted no direct effect on perceived pain, OT was found to modulate the blood oxygen level-dependent response in the ventral striatum for painful versus warm unconditioned stimuli and to decrease activity in the anterior insula (IS) with repeated thermal pain stimuli. Regarding pain anticipation, OT increased responses to CSpain versus CSminus in the nucleus accumbens. Furthermore, in the OT condition increased correct expectations, particularly for the most certain conditioned stimuli (CS)-unconditioned stimuli associations (CSminus and CSpain) were found, as well as greatest deactivations in the right posterior IS in response to the least certain condition (CSwarm) with posterior IS activity and correct expectancies being positively correlated. In conclusion, OT seems to have both a direct effect on pain processing via the ventral striatum and by inducing habituation in the anterior IS as well as on pain anticipation by boostering associative learning in general and the neuronal conditioned fear of pain response in particular. - Perspective - The neuropeptide OT has recently raised the hope to offer a novel avenue for modulating pain experience. This study found OT to modulate pain processing and to facilitate the anticipation of pain, inspiring further research on OT effects on the affective dimension of the pain experience.